Wage-Rate Subsidies for Dislocated Workers - Carl Davidson; Stephen A. Woodbury (W.E. Upjohn Institute for Employment Research, 1995)
An array of innovative policies has been suggested to address more effectively the needs of dislocated workers. In this paper, we model and simulate the impacts of a wage-rate subsidy (or salary supplement) program in which a dislocated worker who becomes reemployed would receive a payment equal to one-half the difference between the wage previously earned and the wage currently earned. The simulations are based on a search model that is institutionally rich and that provides estimates of the impacts of a wage subsidy by incorporating empirical results from the reemployment bonus experiments that were conducted in the mid- to late-1980s. The model includes several groups of workers other than dislocated workers and therefore provides estimates of the degree to which these other workers might be crowded out of jobs by the wage subsidy program. The results suggest that a wage-rate subsidy paid for two years after reemployment would shorten the unemployment spells of dislocated workers by nearly 2 weeks, and would increase employment of dislocated workers by about 900 to 1000 per 100,000 in the labor force. But the simulations also raise the possibility that the gains for dislocated workers could come at the expense of other groups of workers; that is, other groups of workers could experience small increases in unemployment duration, and decreases in employment levels that almost fully offset the gains for dislocated workers. Three factors may mitigate these crowding-out results crowding out is widely dispersed over various groups of non-dislocated workers, the structural changes that result in dislocation of some workers (and drive the need for a policy like a wage subsidy) benefit non-dislocated workers, and the crowding-out results are quite sensitive to one of our assumptions. We also compare the wage-rate subsidy program with a reemployment bonus, and show that the two can be structured so as to give identical results.
Keywords: J0; J6; 330; dislocated; displaced; workers; wage; subsidies; Davidson; Woodbury